1990
DOI: 10.1111/j.1467-8624.1990.tb02886.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hearing Impairment on the Quality of Attachment and Mother-Toddler Interaction

Abstract: In the present study, 41 hearing impaired and 41 hearing toddlers together with their hearing mothers were observed in Ainsworth's Strange Situation and during free play. Both security of attachment and ratings of maternal and toddler behavior during free play were remarkably similar for the hearing impaired and hearing dyads. In addition, security of attachment was related to the ratings of maternal and toddler behavior in a similar way for the hearing impaired and hearing toddlers. The results suggest that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
3
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 23 publications
2
32
3
1
Order By: Relevance
“…Although Lederberg and Mobley (1990) did not find that hearing mothers are more rigid, negative and less likely to respond to their deaf children, they did find that the interactions were shorter, more likely to be interrupted due to break downs in communication, and the communication was likely to be controlled by the parent. Vaccari and Marschark (1997) also have reported that hearing parents are more directive and controlling in their interactions with their deaf children.…”
Section: Contribution Of Family Environment To Pediatric Cochlear Impmentioning
confidence: 73%
See 2 more Smart Citations
“…Although Lederberg and Mobley (1990) did not find that hearing mothers are more rigid, negative and less likely to respond to their deaf children, they did find that the interactions were shorter, more likely to be interrupted due to break downs in communication, and the communication was likely to be controlled by the parent. Vaccari and Marschark (1997) also have reported that hearing parents are more directive and controlling in their interactions with their deaf children.…”
Section: Contribution Of Family Environment To Pediatric Cochlear Impmentioning
confidence: 73%
“…Moreover, both receptive and expressive language skills develop better when parents follow the child’s lead than by redirecting the child’s selective/focused attention to a different referent and labeling it (Kaiser & Hancock, 2003; Kaiser et al, 1996; Yoder, McCathren, Warren, & Watson, 2001). And yet, mothers of children with hearing losses tend to be more controlling and directive, and dominate the interaction with their children with hearing loss than their normal-hearing children (Brinich, 1980; Henggler & Cooper, 1983; Lederberg & Mobley, 1990; Nienhuys et al, 1985; Spencer & Gutfreund, 1990; Vaccari & Marschark, 1997; Wedell-Monnig & Lumley, 1980), for example by initiating interactions and redirecting the child’s attention. Because these control strategies do not support language development in typically developing populations as effectively as strategies that capitalize on joint attention and following a child’s lead, if the same behavior pattern exists in hearing-impaired populations, it could put children with hearing loss at an even greater disadvantage for language development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research on the family’s role in children’s cochlear implantation outcomes has emphasized the role of family in therapy 3,4 , support provided at home 5,6 , use of oral language 7,8,9,10 , family size 7,8 , education level 7 , socioeconomic status 7,8,9 , and several maternal factors including attachment and sensitivity 11,12,13 , qualitative and quantitative linguistic input to the child 14,15 , and sensitivity and self-efficacy 15,16 . Several proximal family factors that are positively related to children’s language development have emerged from these studies 11,12,13,14,15,16 , including the quality of talk between parents and children, mothers’ use of scaffolding, and maternal sensitivity. Expanding upon these established findings, one of the objectives of this study was to measure the impact of more global family factors (e.g., supportiveness and cohesion among family members, and organization and control in the home) on known areas of difficulty in children with cochlear implants (e.g., language and executive function).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, from research on parents of children with physical disabilities, like chronic illnesses, it is known that they treat children younger their age than parents of typically developing children [26]. Regarding sensitivity, research on very young DHH children (from infancy to early childhood) found parents of DHH children and parents of hearing children to be equally sensitive to their children's needs [27], [28], whereas other findings have implied parents of DHH children to be less sensitive [29]. The interpretation of these outcomes is not straightforward though.…”
Section: Introductionmentioning
confidence: 99%